Modal Sosial Community Policing Dalam Menangkal Radikalisme - Sri Suwartiningsih (PAX HUMANA, 2019)
Modern police in the context of "civilization" through community policing raises a new paradigm in building community resilience against crime. It is problem oriented policing to reveal the root problems of religious radicalism. To overcome religious radicalism, it is necessary to build a police and community partnership model known as "community policing". Religious radicalism is a very crucial issue of nation at this time and it is hoped that in the long run a police and community partnership model will be created to create social and legal cohesiveness that can answer the issue of radicalism. Based on this, this research has been carried out on the model of community policing in preventing religious radicalism based on problem oriented policing by involving the community, institutional police, and community institutions in the perspective of social capital. This research uses Qualitative-descriptive with the Constructivism paradigm method to give an understanding of social construction in the partnership of police and society. The theory of social capital is used as an analysis tool. The research area is in the jurisdiction of the Central Java Regional Police, such as in Salatiga City, Semarang Regency, and Semarang City. From the results of the study, the conclusion is that the elements of social capital such as trust, norms and networks became the social capital of community policing between the police and the community in obstructing radicalism.